S19-4: How Does Active Mobility to the Stadium Relate to Perceived Environmental Corporate Social Responsibility? A Survey Among Fans of a Professional Football Club (Baltic Journal of Sport and Health Sciences, 2026)
Background: Professional sports clubs increasingly need to pay attention to, and are evaluated on, their corporate social responsibility (CSR). CSR refers to an organisation’s commitment to operate in an ethical and sustainable manner to contribute positively to society, beyond profit-making and success on the field. A crucial dimension of CSR refers to the environmental impact of the clubs’ activities. One way in which sports clubs can reduce their negative ecological effects is to motivate their fans to come to the games in a physically active way (e.g. by walking or cycling to the venue).Methods: In preparation of the interventions to promote active mobility to the stadium, we surveyed 899 fans of OH Leuven, a professional football team in the Belgium first-division, located in a small-sized university city. The main research aim was to explore the relations between fans’ mobility behaviours and their perceived importance and evaluation of environmental CSR.Results: The results revealed that about half of the fans reported coming to the stadium by means of active mobility: 42.3% by bike and 8.0% on foot (vs. 10.6% by public transportation, 35.8% by car, 3.3% by other means). Overall, fans agreed with the statement that it was important that their club acted in a pro-environmental way (mean (M) = 4.00, standard deviation (SD) = 0.82) on a 5-point Likert scale) and that their club was currently sufficiently acting in a pro-environmental way (M = 3.86, SD = 0.71). Interestingly, active and passive mobility fans did not differ in terms of their perceived importance of environmental CSR. However, active mobility fans were slightly less satisfied with the current environmental actions of their club.Conclusions: The findings further indicated that the active mobility behaviour of fans was mainly determined by more pragmatic reasons (e.g. distance of home to the stadium: M = 4.73 km for the active mobility fans vs. 15.87 km for the passive mobility fans). Interestingly, more than 33% of car-using fans lived less than 10 km from the stadium (14% even 5 km or less), suggesting that interventions to promote cycling should target these fans.